Green synthesis method for supercapacitor porous carbon using one-pot carbonization process with multi-carbon source suitability

CN121306816BActive Publication Date: 2026-10-30SOUTH CHINA NORMAL UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511417925.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-30
Publication Date
2026-10-30
Estimated Expiration
2045-09-30

AI Technical Summary

Technical Problem

[0008]目前尚未有一种活化剂,满足大部分生物质碳源直接一步碳化转化为多孔碳,且多孔碳的性能不受生物质碳源种类的限制,同时具备低腐蚀性,成本低廉,工艺简单的优势

Benefits of technology

[0025](1)本发明使用草酸锌、草酸钾和碱性木质素直接固态混合碳化,草酸锌对碱性木质素的活化效果以介孔和大孔为主,而且活化过程主要发生于700~800℃,与草酸钾的活化过程基本重合,使得介孔和微孔可以同步产生,介孔的生成将导致钾盐拥有更多的活化面积形成微孔,起到共同促进的作用。本发明得到的三维多级多孔碳最高具有2321m2/g的表面积,通过调整多孔碳的孔隙分布,得到的多孔碳在电流密度为1A/g时比电容达到285.3F/g,且在电流密度为10A/g时比电容仍有185.0F/g。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121306816B_ABST
    Figure CN121306816B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of nanomaterials, and particularly relates to a green synthesis method for preparing porous carbon for supercapacitors by one-pot carbonization process. The present application uses an environmentally friendly, inexpensive and low-corrosion activator to develop a simple powder mixing and one-step carbonization process to synthesize three-dimensional multi-stage porous carbon materials with adjustable pore structure. The microporous, mesoporous and macroporous pore distribution of the obtained porous carbon is reasonable, and the highest specific surface area is 2321.4 m 2 / g. In a three-electrode system with 6M KOH as the electrolyte, the specific capacitance reaches 285.3 F / g at a current density of 1 A / g. In a weighing device, the specific capacitance is still 145.1 F / g (1 A / g), 119.1 F / g (10 A / g), and the specific capacitance retention rate is 82.1%. The synthesis method of the present application is also suitable for other biomass carbonization processes and has good applicability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of porous carbon preparation technology for supercapacitors, specifically involving a green synthesis method with multiple carbon sources applicable to the one-pot, one-stage carbonization process for preparing porous carbon for supercapacitors. Background Technology

[0002] Supercapacitors offer higher energy density (greater than 10 Wh / kg) compared to capacitors and higher power density (7000 W / kg) compared to batteries, combining the advantages of both while addressing their shortcomings. They are widely used in energy storage devices. Supercapacitors utilize a variety of electrode materials, among which porous carbon materials are widely used in electric double-layer capacitors (EDLCs) due to their abundant pores, large surface area, and conductivity. The pores of porous carbon materials are classified according to their size into micropores (<2 nm), mesopores (2–50 nm), and macropores (>50 nm). Micropores contribute the most to the specific surface area and are used for ion adsorption and desorption; mesopores connect micropores and facilitate ion transport; and macropores store electrolytes and ions.

[0003] Porous carbon sources originate from fossil carbon sources and biomass carbon sources in nature. Fossil carbon sources are non-renewable, while biomass carbon sources are environmentally friendly and renewable. The three most abundant biomass in nature are cellulose, hemicellulose, and lignin. Lignocellulose, formed by the combination of these three, is the most abundant organic carbon source in nature and a major component of terrestrial plants. Cellulose is the most abundant organic compound in nature, followed by lignin, which produces 70 million tons annually. Despite its vast reserves, it has not been widely converted into high-value-added products. Many researchers have developed various processes to convert biomass into porous carbon, such as gas activation, chemical activation, electrospinning, soft template pore-forming, hydrothermal carbonization, and high-temperature carbonization. Among these, gas activation has limited pore-forming effect, electrospinning equipment is costly and has low output, and the electrospinning method requires large molecules with chain structures, which limits the molecular structure of biomass. Soft template pore-forming involves electrostatic self-assembly at the molecular level, resulting in low pore-forming effect and difficulty in control. Chemical activation is widely used due to its high pore-forming efficiency and simple process.

[0004] Traditional chemical activation methods use KOH as an activator. After pre-carbonizing biomass, it is dried and mixed with KOH using a wet process, followed by a second carbonization to obtain porous carbon with a specific surface area reaching 2000 m². 2For example, Zhang et al. obtained porous carbon with a specific capacitance of 286.7 F / g (current density 0.2 A / g) in 6M KOH electrolyte using KOH activation of lignin carbon. This method is applicable to various pre-carbonized biomass carbon sources. However, the large dosage, high corrosiveness, equipment degradation, and environmental toxicity of KOH greatly limit its practical application. Cui et al. experienced a violent reaction during KOH activation of hydrothermal carbon, resulting in severe corrosion of the quartz tube and destruction of the product. Furthermore, KOH activation generally requires two carbonization processes for biomass, which is cumbersome.

[0005] Compared to potassium hydroxide, some potassium compounds (potassium carbonate, potassium oxalate, potassium acetate, and potassium sulfate) retain some activation effects while reducing corrosivity. Xi et al. investigated the activation effects of different potassium salts on enzymatically hydrolyzed lignin. By impregnating potassium salts with enzymatically hydrolyzed lignin and then directly carbonizing it, they found that potassium oxalate produced the highest proportion of micropores at an activation temperature of 800℃, potassium carbonate showed the best activation effect, followed by KOH. Wang et al. analyzed the activation mechanism of KOH, finding that KOH is a highly reactive compound that reacts with biomass at lower temperatures, leading to over-activation, pore collapse, and a decrease in specific surface area. Potassium carbonate and potassium oxalate, due to their lower corrosivity, can be activated with enzymatically hydrolyzed lignin in a single carbonization step to obtain porous carbon. Singh et al. also investigated the potassium salt activation process for biomass, finding that a single carbonization step was significantly simpler than a two-step carbonization process. However, the porous carbon obtained from potassium salts has a pore size distribution concentrated below 3 nm, which can easily hinder ion transport in supercapacitor applications.

[0006] Potassium oxalate, as an activator, offers advantages such as low corrosivity, high micropore selectivity, and the ability to achieve activation in a single carbonization step. The goal is to find another activator that also possesses low corrosivity and mesopore selectivity, combining with the activation effect of potassium oxalate during biomass activation to achieve a one-step carbonization process that forms a three-dimensional hierarchical porous structure. This method allows for pore size control based on the characteristics of the biomass, making it suitable for porous carbon production from most biomass sources.

[0007] Fu et al. used a solution self-assembly method to obtain zinc oxalate and lignin sulfonate complexes. The porous carbon obtained after carbonization had a layered structure rich in mesopores and a specific surface area of ​​1268 m². 2 The mesoporous pore volume ratio is 67.6%. However, solution self-assembly methods require biomass to be water-soluble and amphiphilic, which limits the use of biomass. This is because naturally occurring biomass mainly exists in the form of lignocellulose, which has a complex molecular structure, large molecular weight, and is poorly soluble in water, making it unsuitable for solution self-assembly composite activators. A cumbersome separation process is required to obtain water-soluble lignin and water-insoluble cellulose.

[0008] Currently, there is no activator that can directly carbonize most biomass carbon sources into porous carbon in one step, and the performance of porous carbon is not limited by the type of biomass carbon source. It also has the advantages of low corrosivity, low cost, and simple process. Summary of the Invention

[0009] To overcome the shortcomings of the existing technology, this invention provides a green synthesis method applicable to multiple carbon sources for preparing porous carbon for supercapacitors using a one-pot, one-step carbonization process. This invention utilizes environmentally friendly, inexpensive, and low-corrosion activators to develop a simple powder mixing and one-step carbonization process to synthesize three-dimensional hierarchical porous carbon materials with controllable pore structures. The resulting porous carbon exhibits a reasonable distribution of micropores, mesopores, and macropores, with the highest reaching 2321.4 μm. 2 With a high specific surface area of ​​ / g, the specific capacitance reaches 285.3 F / g in a three-electrode system using 6M KOH as the electrolyte and a current density of 1 A / g. In the weighing apparatus, the specific capacitance remains at 145.1 F / g (1 A / g) and 119.1 F / g (10 A / g), exhibiting a specific capacitance retention rate of 82.1%. The synthesis method of this invention is also suitable for other biomass carbonization processes, demonstrating good applicability.

[0010] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0011] This invention provides a green synthesis method for preparing porous carbon for supercapacitors using a one-pot, single-stage carbonization process, which is applicable to multiple carbon sources. The preparation method includes the following steps:

[0012] (1) Mix the biomass raw materials with the activator to obtain a mixed raw material;

[0013] (2) Carbonize the mixed raw materials in an inert gas environment, cool, grind, acid wash, water wash, and dry to obtain porous carbon;

[0014] The activator is a mixture of zinc oxalate and potassium oxalate.

[0015] Further, in step (1), the mass ratio of the biomass raw material to the activator is 1:0.9-1:2.6.

[0016] Further, in step (1), the mass ratio of zinc oxalate to potassium oxalate is 1:1.6-1:8.

[0017] Further, in step (1), the mass ratio of the biomass raw material, zinc oxalate and potassium oxalate is 10:1:8-10:10:16.

[0018] Furthermore, in step (2), the carbonization is carried out by a programmed temperature increase method, from room temperature to 300-500℃ and held for 0.5-1.5 hours, and then heated to 700-1000℃ and held for 1-3 hours.

[0019] Furthermore, in step (2), the programmed temperature rise refers to raising the temperature from room temperature to 400°C and holding it for one hour, then raising it to 800°C and holding it for two hours.

[0020] Furthermore, the heating rate is 3–15 °C / min. -1 .

[0021] Furthermore, in step (2), the flow rate of the inert gas is 100–300 ml / min. -1 .

[0022] Furthermore, in step (2), the acid washing refers to washing with HCl solution by stirring.

[0023] Furthermore, in step (2), the water washing refers to washing with deionized water until neutral.

[0024] Compared with the prior art, the beneficial effects of the present invention are:

[0025] (1) This invention uses direct solid-state mixed carbonization of zinc oxalate, potassium oxalate, and alkaline lignin. The activation effect of zinc oxalate on alkaline lignin is mainly mesoporous and macroporous, and the activation process mainly occurs at 700-800℃, which basically overlaps with the activation process of potassium oxalate. This allows mesopores and micropores to be generated simultaneously. The formation of mesopores will lead to potassium salt having more activation area to form micropores, playing a synergistic role. The three-dimensional multi-level porous carbon obtained by this invention has a maximum size of 2321 μm. 2 By adjusting the pore distribution of porous carbon, the surface area of ​​the porous carbon was / g. The resulting porous carbon achieved a specific capacitance of 285.3 F / g at a current density of 1 A / g, and still had a specific capacitance of 185.0 F / g at a current density of 10 A / g.

[0026] (2) By adjusting the amount and ratio of the two activators, the pore size and range of porous carbon can be controlled, verifying that this method can be applied to other untreated biomass. In this invention, sugarcane bagasse is used as a carbon source. The main component of sugarcane bagasse is lignocellulose, of which cellulose, hemicellulose and lignin are about 40%, 24% and 33% respectively. It is a typical lignocellulose in nature. By rationally allocating the amount and ratio of zinc oxalate and potassium oxalate, the porous carbon prepared as an electrode has a specific capacitance of 352.0 F / g at a current density of 1 A / g, and still has a capacitance of 177.2 F / g at a current density of 20 A / g. Attached Figure Description

[0027] Figure 1 This is a process flow diagram of porous carbon synthesis in Example 1.

[0028] Figure 2 The images show the infrared spectrum (a), XPS spectrum (b), and XPS spectrum (c) of the alkaline lignin in Example 1.

[0029] Figure 3 The N2 adsorption-desorption curves (a) and pore size distribution (b) of the porous carbon PC-10-800-none in Comparative Example 1 are shown.

[0030] Figure 4 The N2 adsorption-desorption curves (a) and pore size distribution diagrams (b) of porous carbon PC-11-600-ZnC2O4 in Comparative Example 2, porous carbon PC-11-700-ZnC2O4 in Comparative Example 3, porous carbon PC-11-750-ZnC2O4 in Comparative Example 4, and porous carbon PC-11-800-ZnC2O4 in Comparative Example 5 are shown.

[0031] Figure 5 The porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in Example 1 and the porous carbon in Comparative Example 1

[0032] N2 adsorption-desorption curves (a), pore size distribution diagrams (b), and Raman spectra (c) of porous carbon PC-10-800-none, porous carbon PC-11-800-ZnC2O4 in Comparative Example 5, porous carbon PC-12-800-KOH in Comparative Example 6, and porous carbon PC-11-800-K3[Fe(C2O4)3] in Comparative Example 7.

[0033] Figure 6 The images are SEM images (a) and (b) of porous carbon PC-10-800-none in Comparative Example 1, (c) and (d) of porous carbon PC-11-800-ZnC2O4 in Comparative Example 5, (e) and (f) of porous carbon PC-12-800-KOH in Comparative Example 6, (g) and (h) of porous carbon PC-11-800-K3[Fe(C2O4)3] in Comparative Example 7, and (i) and (j) of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in Example 1.

[0034] Figure 7 Thermogravimetric analysis (TGA) diagrams of zinc oxalate activator and alkaline lignin in Comparative Example 5 (a) and potassium ferric oxalate activator and alkaline lignin in Comparative Example 7 (b) are shown.

[0035] Figure 8XPS spectra of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in Example 1 (a), XPS spectra of C 1s (b), XPS spectra of O 1s (c), and XPS spectra of porous carbon YP-50F (d).

[0036] Figure 9 The CV curves (a) and GCD curves (b) of porous carbon PC-10-800-none in the three-electrode system are shown in Comparative Example 1, the CV curves (c) and GCD curves (d) of porous carbon PC-11-800-ZnC2O4 in the three-electrode system are shown in Comparative Example 5, the CV curves (e) and GCD curves (f) of porous carbon PC-12-800-KOH in the three-electrode system are shown in Comparative Example 6, the CV curves (g) and GCD curves (h) of porous carbon PC-11-800-K3[Fe(C2O4)3] in the three-electrode system are shown in Comparative Example 7, and the CV curves (i) and GCD curves (j) of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in the three-electrode system are shown in Example 1.

[0037] Figure 10 The porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in Example 1 and the porous carbon in Comparative Example 1

[0038] Comparison of GCD (a), CV (b), and EIS (c) of porous carbon PC-10-800-none, porous carbon PC-11-800-ZnC2O4 in Comparative Example 5, porous carbon PC-12-800-KOH in Comparative Example 6, and porous carbon PC-11-800-K3[Fe(C2O4)3] in Comparative Example 7 in a three-electrode system.

[0039] Figure 11 The images show the CV curve (a), GCD curve (b), EIS spectrum (c), and 5000 charge-discharge cycle diagram (d) of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in the Swagelok device in Example 1.

[0040] Figure 12 The images show the GCD curve (a), CV curve (b), current density versus capacity (c), and EIS spectrum (d) of porous carbon PC-bagasse in the three-electrode system in Example 2. Detailed Implementation

[0041] The specific embodiments of the present invention will be further described below. It should be noted that these descriptions are for the purpose of aiding understanding the present invention, but do not constitute a limitation thereof. Furthermore, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0042] Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods, and the experimental materials used in the following embodiments are all available through conventional commercial channels.

[0043] Example 1: Preparation of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4

[0044] The synthesis process flow diagram of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 is shown below. Figure 1 As shown, 5g of alkaline lignin (Aladdin), 0.5g of zinc oxalate powder (Aladdin ≥ 99%) and 4g of potassium oxalate powder (Aladdin ≥ 99%) were simply stirred and mixed, transferred to an alumina boat, and then transferred to a tube furnace. The furnace was first evacuated, then nitrogen was introduced, repeated three times to purge air, and the furnace was heated to 200ml / min. -1 Under a nitrogen atmosphere with a flow rate of [flow rate missing], the heating program was set as follows: heating from room temperature to 400℃ and holding for one hour to allow the alkaline lignin and activator to mix thoroughly, then heating to 800℃ and holding for two hours, with a heating rate of 10℃ / min. -1 After the equipment cools down, the obtained porous carbon is ground into powder and transferred to a beaker. 50 ml of 1M HCl solution is prepared and the mixture is stirred and washed at 300 r for 2 h. The resulting solution is filtered, and the porous carbon solid is retained. It is washed with deionized water until neutral and dried to obtain porous carbon PC-10:1:8-800-KC2O4&ZnC2O4.

[0045] The functional group composition of alkaline lignin was analyzed using Fourier transform infrared spectroscopy (Nicolet 6700) with a scanning wavelength range of 650–4000 cm⁻¹. The resulting infrared spectra are shown below. Figure 2 As shown in a, the wavenumber is 3307 cm⁻¹. -1 An absorption peak for the stretching vibration of -OH appears nearby, with a wavenumber of 767 cm⁻¹. -1 Nearby, out-of-plane bending absorption peaks of substituted benzene (CH) are observed, with wavenumbers ranging from 1000 to 1200 cm⁻¹. -1 An absorption peak for the stretching vibration of -COC- appears, with a wavenumber of 1410 cm⁻¹. -1 A symmetric stretching vibration peak of phenol-ionized CO- appears nearby, with a wavenumber of 1565 cm⁻¹. -1The presence of vibrational absorption peaks in the carbon skeleton of ionized benzene rings nearby indicates that alkaline lignin contains a large number of phenolic hydroxyl groups and aromatic rings cross-linked by ether bonds. The elemental composition and valence state of alkaline lignin were analyzed using X-ray photoelectron spectroscopy (Thermo Kalpha), and the resulting XPS spectrum is shown below. Figure 2 As shown in b, the XPS full-spectrum semi-quantitative analysis of alkaline lignin reveals a high carbon content of 73.51%, providing an abundant carbon source for porous carbon formation. Simultaneously, 23.77% of the oxygen is converted into CO2 and H2O gases during carbonization and released. Furthermore, alkaline lignin contains 2.74% sodium in the form of salt, which erodes the carbon during carbonization, expanding the surface area of ​​the porous carbon. The obtained XPS spectrum of C1s of alkaline lignin is shown below. Figure 2 As shown in Figure c, some carbon peaks are in the range of 288–290 eV, which can be inferred to be carbonate peaks, because the wavenumbers in the infrared spectrum are 1600–1700 cm⁻¹. -1 No organic -C=O absorption peaks were found within the range.

[0046] The elemental composition and valence state of porous carbon PC-10:1:8-800-KC2O4 & ZnC2O4 were analyzed using X-ray photoelectron spectroscopy (Thermo Kalpha). The XPS spectra of porous carbon PC-10:1:8-800-KC2O4 & ZnC2O4 are shown below. Figure 8 As shown in Figure a, the XPS spectra of C1s of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 are as follows: Figure 8 As shown in b, the XPS spectrum of O1s of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 is as follows. Figure 8 As shown in c, the XPS spectrum of the popular porous carbon YP-50F is as follows. Figure 8 As shown in Figure d, the porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 contains C and O elements. The O element manifests as -CO, -C=O, and -COOH linked to the carbon framework, with almost no impurities. Compared to the best-selling YP-50F porous carbon on the market, which has an extremely high carbon content of 95.4%, this is beneficial for imparting electronic conductivity and cycle stability to the porous carbon. The presence of oxygen atoms can enhance the wettability between the carbon material surface and the electrolyte.

[0047] Example 2: Preparation of porous carbon PC-bagasse

[0048] Dissolve 3.2g of potassium oxalate (Aladdin ≥ 99%) in 10ml of deionized water, add 2g of sugarcane bagasse (provided by Guangxi Normal University for Nationalities), stir and impregnate. Then add 2g of zinc oxalate powder (Aladdin ≥ 99%), mix and impregnate. After vacuum drying, transfer to a corundum boat. Transfer the corundum boat to a tube furnace, first evacuate and then purge with nitrogen three times to remove air. Heat at 200ml / min. -1 Under a nitrogen atmosphere with a flow rate of [flow rate missing], the heating program was set as follows: heating from room temperature to 400℃ and holding for one hour, then heating to 800℃ and holding for two hours, with a heating rate of 10℃ / min. -1 After the equipment cools down, the obtained porous carbon is ground into powder and transferred to a beaker. 50 ml of 1 M HCl solution is prepared and the mixture is stirred and washed at 300 r for 2 h. The resulting solution is filtered, and the porous carbon solid is retained. It is washed with deionized water until neutral and dried to obtain porous carbon PC-bagasse.

[0049] Comparative Example 1: Preparation of porous carbon PC-10-800-none

[0050] Transfer 5g of aladdin to a corundum boat, then transfer the corundum boat to a tube furnace. First, evacuate the furnace, then purge with nitrogen three times to remove air. Heat at 200ml / min. -1 Under a nitrogen atmosphere with a flow rate of [flow rate missing], the heating program was set as follows: heating from room temperature to 400℃ and holding for one hour, then heating to 800℃ and holding for two hours, with a heating rate of 10℃ / min. -1 After the equipment cools down, the obtained porous carbon is ground into powder and transferred to a beaker. 50 ml of 1 M HCl solution is prepared and the mixture is stirred and washed at 300 r for 2 h. The resulting solution is filtered, and the porous carbon solid is retained. It is washed with deionized water until neutral and dried to obtain porous carbon PC-10-800-none.

[0051] The specific surface area and pore size distribution of porous carbon PC-10-800-none were analyzed using a multi-station extended fully automated specific surface area and pore size analyzer (ASAP 2460). The degassing temperature was 250℃, and the degassing time was 10 h. Adsorption tests were performed using N2 at 196℃ and CO2 at 0℃. The N2 adsorption-desorption curves of porous carbon PC-10-800-none are shown below. Figure 3 As shown in Figure a, the pore size distribution is as follows Figure 3 As shown in b, the presence of sodium salt and oxygen-containing photoenergy groups enables PC-10-800-none to achieve a specific surface area of ​​1070 m². 2 / g, but due to the self-activation of alkaline lignin during the activation process, the resulting porous carbon has a pore structure dominated by micropores, accompanied by a small amount of mesopores and macropores.

[0052] Comparative Example 2: Preparation of porous carbon PC-11-600-ZnC2O4

[0053] Simply mix 5g of alkaline lignin (Aladdin) and 5g of zinc oxalate powder (Aladdin ≥ 99%), transfer to an alumina boat, then transfer the alumina boat to a tube furnace. First, evacuate the furnace, then purge with nitrogen three times to remove air. Heat at 200ml / min. -1 Under a nitrogen atmosphere with a flow rate of [flow rate missing], the heating program was set as follows: heating from room temperature to 400℃ and holding for one hour to allow the alkaline lignin and activator to mix thoroughly, then heating to 600℃ and holding for two hours, with a heating rate of 10℃ / min. -1 After the equipment cools down, the obtained porous carbon is ground into powder and transferred to a beaker. 50 ml of 1M HCl solution is prepared and the mixture is stirred and washed at 300 r for 2 h. The resulting solution is filtered, and the porous carbon solid is retained. It is washed with deionized water until neutral and dried to obtain porous carbon PC-11-600-ZnC2O4.

[0054] Comparative Example 3: Preparation of porous carbon PC-11-700-ZnC2O4

[0055] Simply mix 5g of alkaline lignin (Aladdin) and 5g of zinc oxalate powder (Aladdin ≥ 99%), transfer to an alumina boat, then transfer the alumina boat to a tube furnace. First, evacuate the furnace, then purge with nitrogen three times to remove air. Heat at 200ml / min. -1 Under a nitrogen atmosphere with a flow rate of [missing information], the heating program was set as follows: heating from room temperature to 400℃ and holding for one hour to allow the alkaline lignin and activator to mix thoroughly, then heating to 700℃ and holding for two hours, with a heating rate of 10℃ / min. -1 After the equipment cools down, the obtained porous carbon is ground into powder and transferred to a beaker. 50 ml of 1 M HCl solution is prepared and the mixture is stirred and washed at 300 r for 2 h. The resulting solution is filtered, and the porous carbon solid is retained. It is washed with deionized water until neutral and dried to obtain porous carbon PC-11-700-ZnC2O4.

[0056] Comparative Example 4: Preparation of porous carbon PC-11-750-ZnC2O4

[0057] Simply mix 5g of alkaline lignin (Aladdin) and 5g of zinc oxalate powder (Aladdin ≥ 99%), transfer to an alumina boat, then transfer the alumina boat to a tube furnace. First, evacuate the furnace, then purge with nitrogen three times to remove air. Heat at 200ml / min. -1 Under a nitrogen atmosphere with a flow rate of [missing information], the heating program was set as follows: heating from room temperature to 400℃ and holding for one hour to allow the alkaline lignin and activator to mix thoroughly, then heating to 750℃ and holding for two hours, with a heating rate of 10℃ / min. -1After the equipment cools down, the obtained porous carbon is ground into powder and transferred to a beaker. 50 ml of 1 M HCl solution is prepared and the mixture is stirred and washed at 300 r for 2 h. The resulting solution is filtered, and the porous carbon solid is retained. It is washed with deionized water until neutral and dried to obtain porous carbon PC-11-750-ZnC2O4.

[0058] Comparative Example 5: Preparation of porous carbon PC-11-800-ZnC2O4

[0059] Simply mix 5g of alkaline lignin (Aladdin) and 5g of zinc oxalate powder (Aladdin ≥ 99%), transfer to an alumina boat, then transfer the alumina boat to a tube furnace. First, evacuate the furnace, then purge with nitrogen three times to remove air. Heat at 200ml / min. -1 Under a nitrogen atmosphere with a flow rate of [flow rate missing], the heating program was set as follows: heating from room temperature to 400℃ and holding for one hour to allow the alkaline lignin and activator to mix thoroughly, then heating to 800℃ and holding for two hours, with a heating rate of 10℃ / min. -1 After the equipment cools down, the obtained porous carbon is ground into powder and transferred to a beaker. 50 ml of 1M HCl solution is prepared and the mixture is stirred and washed at 300 r for 2 h. The resulting solution is filtered, and the porous carbon solid is retained. It is washed with deionized water until neutral and dried to obtain porous carbon PC-11-600-ZnC2O4.

[0060] Comparative Example 6: Preparation of porous carbon PC-12-800-KOH

[0061] Transfer 5g of aladdin to a corundum boat, then transfer the corundum boat to a tube furnace. First, evacuate the furnace, then purge with nitrogen three times to remove air. Heat at 200ml / min. -1 Under a nitrogen atmosphere with a flow rate of [flow rate missing], the heating program was set as follows: heat from room temperature to 400℃ and hold for one hour, add 10g of potassium hydroxide (Macklin 99.99% electronic grade), mix and grind, then heat to 800℃ and hold for two hours, with a heating rate of 10℃ / min. -1 After the equipment cools down, the obtained porous carbon is ground into powder and transferred to a beaker. 50 ml of 1 M HCl solution is prepared and the mixture is stirred and washed at 300 r for 2 h. The resulting solution is filtered, and the porous carbon solid is retained. It is washed with deionized water until neutral and dried to obtain porous carbon PC-12-800-KOH.

[0062] Comparative Example 7: Preparation of porous carbon PC-11-800-K3[Fe(C2O4)3]

[0063] 5g of alkaline lignin (Aladdin), 5g of potassium ferric oxalate (K3[Fe(C2O4)3]) (Aladdin ≥ 99%) and 4g of potassium oxalate powder (Aladdin ≥ 99%) were simply stirred and mixed, then transferred to an alumina boat. The alumina boat was then transferred to a tube furnace, and the furnace was evacuated and then purged with nitrogen three times to remove air. The furnace was heated to 200ml min. -1 Under a nitrogen atmosphere with a flow rate of [flow rate missing], the heating program was set as follows: heating from room temperature to 400℃ and holding for one hour to allow the alkaline lignin and activator to mix thoroughly, then heating to 800℃ and holding for two hours, with a heating rate of 10℃ / min. -1 After the equipment cools down, the obtained porous carbon is ground into powder and transferred to a beaker. 50 ml of 1 M HCl solution is prepared and the mixture is stirred and washed at 300 r for 2 h. The resulting solution is filtered, and the porous carbon solid is retained. It is washed with deionized water until neutral and dried to obtain porous carbon PC-11-800-K3[Fe(C2O4)3].

[0064] Test Example 1: Material Characterization Test

[0065] The specific surface area and pore size distribution of porous carbon in Examples 1, 1, 2, 3, 4, 5, 6, and 7 were analyzed using a multi-station extended fully automated specific surface area and pore size analyzer (ASAP 2460). The degassing temperature was 250℃, and the degassing time was 10 h. Adsorption tests were conducted using N2 at 196℃ and CO2 at 0℃. The ash content of porous carbon was measured according to the Chinese national standard GB / T 12496.3-1999. The ignition temperature in air was 650±20℃, and the weight measured after constant weight was the ash weight. The specific surface area and ash content of the obtained porous carbon are shown in Table 1.

[0066] Table 1

[0067]

[0068] The widely used method for preparing lignin-derived porous carbon generally involves pre-carbonizing lignin, then grinding and mixing it with KOH, followed by re-carbonization, acid washing, and drying to obtain porous carbon. Zinc oxalate can be used to prepare porous carbon from alkaline lignin through a simple powder mixing process and a single carbonization step. During the direct carbonization of alkaline lignin, a molten state occurs, and the release of gas in this state leads to expansion, making the carbonization volume uncontrollable. Directly adding potassium salts or KOH for carbonization exacerbates the expansion and reduces the carbon yield. Adding zinc oxalate salts inhibits the melting phenomenon and enhances cross-linking. Due to its in-situ template effect and gas-phase exfoliation, zinc oxalate promotes the formation of micropores, mesopores, and macropores during the carbonization process of alkaline lignin. As shown in Table 1, compared to direct carbonization of alkaline lignin, using zinc oxalate as an activator increases the specific surface area by approximately 500 m². 2 / g, the area of ​​mesopores, macropores, and micropores increased significantly, and the specific pore volume increased from 0.78cm³. 3 g -1 Increased to 2.12cm 3 g -1 .

[0069] The specific surface area and pore size distribution of porous carbon in Comparative Examples 2, 3, 4, and 5 were analyzed using a multi-station extended fully automated specific surface area and pore size analyzer (ASAP 2460). The degassing temperature was 250℃, and the degassing time was 10 h. Adsorption tests were performed using N2 at 196℃ and CO2 at 0℃. The N2 adsorption-desorption curves for porous carbon PC-11-600-ZnC2O4 in Comparative Example 2, PC-11-700-ZnC2O4 in Comparative Example 3, PC-11-750-ZnC2O4 in Comparative Example 4, and PC-11-800-ZnC2O4 in Comparative Example 5 are shown below. Figure 4 As shown in Figure a, the pore size distribution diagram is as follows: Figure 4 As shown in Figure b, it can be seen that at a temperature of 600℃, although zinc oxalate decomposes and releases CO2 and CO gas around 400℃, the specific surface area of ​​the lignin carbonized with alkaline solution is only 285.7 m². 2 / g, but it provides the initial surface area for alkaline lignin, giving the porous carbon a looser structure, facilitating subsequent erosion of the porous carbon at higher temperatures. The activation and pore-forming process mainly occurs between 700 and 800℃. As the temperature increases, the specific surface area increases, and the pore size also widens. At 700℃, a large number of micropores and some mesopores and macropores are generated. At 750℃, micropores with a pore size of less than 1nm decrease, while micropores with a pore size of around 2nm increase. The surface area of ​​the micropores actually increases, presumably because smaller micropores become larger at this time. At 800℃, the micropore area actually decreases, while the surface area of ​​mesopores and macropores increases significantly, presumably because the micropores are further activated into mesopores and macropores at this stage. At this point, there are suitable micropores, mesopores, and macropores. The specific pore volume reaches 2.12 cm³. 3 g -1 This indicates that the porosity is already extremely high. However, at higher temperatures, the number of micropores decreases, leading to a sharp reduction in specific surface area, while carbon erosion becomes more severe.

[0070] The specific surface area and pore size distribution of porous carbon in Examples 1, 1, 5, 6, and 7 were analyzed using a multi-station extended fully automated surface area and pore size analyzer (ASAP 2460). The degassing temperature was 250°C, and the degassing time was 10 h. Adsorption tests were performed using N2 at 196°C and CO2 at 0°C. Defect bands and graphitic bands in the porous carbon were analyzed using Raman spectroscopy (LabRam HR Evolution HORIBA) in the wavelength range of 500–2500 cm⁻¹. -1 The N2 adsorption-desorption curves of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in Example 1, porous carbon PC-10-800-none in Comparative Example 1, porous carbon PC-11-800-ZnC2O4 in Comparative Example 5, porous carbon PC-12-800-KOH in Comparative Example 6, and porous carbon PC-11-800-K3[Fe(C2O4)3] in Comparative Example 7 are shown below. Figure 5 As shown in Figure a, the aperture distribution diagram is as follows: Figure 5 As shown in b, the Raman spectrum is as follows Figure 5As shown in Figure c, it can be seen that sample PC-10:1:8-800-KC2O4&ZnC2O4 has the highest adsorption value, and its adsorption curve is similar to a type I adsorption curve. The adsorption amount increases sharply within a relatively low pressure range, exhibiting obvious microporous adsorption behavior. However, within a relatively high pressure range, it shows an exponential growth curve and exhibits adsorption-desorption hysteresis loops, demonstrating mesoporous and macroporous adsorption behavior. In contrast, the adsorption-desorption curve of sample PC-12-800-KOH does not show a clear mesoporous structure. PC-11-800-K3[Fe(C2O4)3] produces more abundant pores below 5 nm, while retaining suitable mesopores and macropores for storing electrolyte and improving ion transport rate. However, since the synthesis of potassium iron oxalate requires further processing, and the iron(III) oxide template left during carbonization is difficult to remove with acid, and the pore size distribution generated by carbonization is relatively fixed, a mixed activator of potassium oxalate and zinc oxalate is used to regulate the pore distribution. The gases produced by oxalates at high temperatures act as gas-phase separators for carbon materials, and are relatively mild, not corroding the carbon, and do not introduce impurities after decomposition. Potassium oxalate decomposes, leaving potassium carbonate, and the introduced potassium ions corrode the carbon to a certain extent, creating numerous micropores. Combined with the pore-forming effect of zinc oxalate, by controlling the ratio of the two oxalates, three-dimensional hierarchical porous carbon materials with adjustable pore size distribution can be obtained. As shown in Table 1, the specific pore volume of the sample PC-10:1:8-800-KC2O4&ZnC2O4 further increased to 2.54 cm³. 3 g -1 Compared with sample PC-11-800-K3[Fe(C2O4)3], the surface area of ​​micropores and mesopores further increased. The pore size distribution of PC-12-800-KOH was primarily micropores, with a specific surface area of ​​2092 m². 2 / g, with a pore volume of only 1.32cm³. 3 g -1 The Raman diffraction peaks show two characteristic bands with a wavenumber of 1400 cm⁻¹. -1 The surrounding area exhibits a defect structure of carbon, 1600 cm⁻¹ -1 The surrounding area exhibits a carbon-based graphite structure. It can be seen that samples PC-11-800-ZnC2O4 and PC-10:1:8-800-KC2O4&ZnC2O4, with a higher proportion of mesopores and macropores, show a higher Id / Ig ratio, indicating that the abundant three-dimensional porous structure will guide more carbon defects. The Id / Ig ratio of sample PC-10:1:8-800-KC2O4&ZnC2O4 is... d / I g The ratio reached an astonishing 3.316, indicating that by designing the pore structure and adjusting the appropriate ratio of micropores, mesopores and macropores, carbon defects can be maximized, resulting in a functional three-dimensional hierarchical porous carbon.

[0071] The surface morphology of the porous carbon material was observed using a field emission scanning electron microscope (HITACHI SU8600). The SEM image of the porous carbon PC-10-800-none in Comparative Example 1 is shown below. Figure 6 As shown in a and b, the SEM images of porous carbon PC-11-800-ZnC2O4 in Comparative Example 5 are as follows: Figure 6 As shown in c and d, the SEM images of porous carbon PC-12-800-KOH in Comparative Example 6 are as follows: Figure 6 As shown in e and f, the SEM images of porous carbon PC-11-800-K3[Fe(C2O4)3] in Comparative Example 7 are as follows: Figure 6 As shown in g and h, the SEM images of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in Example 1 are as follows: Figure 6 As shown in i and j, it can be seen that the pore size distribution of sample PC-10-800-none is poor due to the lack of activator, and some surfaces show smooth carbon planes. Compared with PC-11-800-ZnC2O4, PC-12-800-KOH, and PC-11-800-K3[Fe(C2O4)3], the pore distribution of sample PC-10:1:8-800-KC2O4&ZnC2O4 is more uniform and reasonable, and the pores are open.

[0072] Thermogravimetric analysis was performed on the zinc oxalate activator and basic lignin in Comparative Example 5, and the results are as follows: Figure 7 As shown in Figure a, calculations show that the weight loss process of zinc oxalate around 200℃ corresponds to the removal of water of crystallization, while the weight loss process around 400℃ corresponds to the decomposition of zinc oxalate, releasing CO and CO2 gases. The weight loss processes of alkaline lignin occur at 200–300℃, 400–500℃, and 700–800℃. The weight loss at 200–300℃ mainly corresponds to the decomposition of oxygen-containing functional groups and small molecular branches on the surface of alkaline lignin; the weight loss at 400–500℃ corresponds to the breaking and decomposition of ether bonds within the lignin, with aromatic rings beginning to dehydrate, cross-link, and carbonize; and the weight loss at 700–800℃ corresponds to the decomposition of ester bonds, further reducing oxygen content and simultaneously forming more pores. Thermogravimetric analysis was performed on alkaline lignin with potassium ferric oxalate activator in Comparative Example 7, and the results are as follows: Figure 7 As shown in b, gas-phase separation occurs during the initial carbonization stage, forming an iron oxide template. At higher temperatures, potassium ions enter the initially formed pores and react with carbon to exert an erosive effect, forming more abundant micropores with a specific surface area reaching 2321.4 m². 2 / g. It is known that the template effect and gas-phase separation of zinc oxalate play a major role in the formation of mesopores and macropores; however, abundant micropores are the primary factor in increasing the specific surface area of ​​porous carbon. An excessively high proportion of mesopores and macropores will reduce the specific surface area of ​​porous carbon. In existing mainstream literature, methods for creating pores in biomass mostly involve pre-carbonizing the biomass and then mixing it with KOH or potassium salts using wet or dry methods. The porous carbon obtained by this method is mainly attributed to the erosive effect of potassium ions on carbon, forming abundant microporous carbon. However, this method requires a secondary carbonization process, and the pores formed are mainly concentrated in micropores, lacking mesopores and macropores. This invention combines the erosive effect of potassium salts with the template and gas-phase separation effects of zinc oxalate to synthesize three-dimensional hierarchical porous carbon with controllable pore distribution in a one-step carbonization process. During the carbonization process, potassium ferric oxalate exhibits behavior similar to zinc oxalate.

[0073] Test Example 2: Electrochemical Test

[0074] Cut the clean nickel foam (lithium-ionized, 1.5mm thick) current collector into 1×2cm pieces. 2 The sample was a rectangular parallelepiped, and its weight was measured as m0. 100 mg of porous carbon sample was weighed and added to 2 ml of 5 M HNO3, then kept at 70°C for 4 hours to improve the wettability of the porous carbon surface. The porous carbon was filtered, washed with deionized water, and dried in a vacuum drying oven at 80°C for 3 hours. The obtained porous carbon was mixed with acetylene black (lithium oxide) and polytetrafluoroethylene micropowder (Macklin, average particle size 1.6 μm) in a ratio of 8:1:1. 2 ml of anhydrous ethanol (Macklin 99.5%) was added, and the mixture was sonicated at 70% power for 10 min in a cell disruptor, followed by magnetic stirring for 1 h. After thorough mixing, the mixture was coated onto half of a pre-cut nickel foam electrode. The resulting nickel foam electrode was thoroughly dried in a vacuum drying oven at 80°C for 3 hours, then pressed into a thin sheet using a plate vulcanizer at 10 MPa pressure. The electrode weight was measured as m1. The mass m of the active material was calculated using the following formula:

[0075] m = (m1 - m0) × 80%

[0076] Electrode preparation for the two-electrode system: cut nickel foam into discs with a diameter of 1 cm. The remaining preparation steps are the same as those for the three-electrode system. The active material loading of the two electrodes is 3-6 mg.

[0077] The three-electrode system was tested using a Princeton electrochemical workstation. The reference electrode was a saturated calomel electrode, the counter electrode was a platinum sheet electrode, and a nickel foam electrode was clamped with a platinum sheet electrode clamp as the working electrode. A 6MKOH solution was used as the electrolyte to form the three-electrode system. Cyclic voltammetry (CV) voltage scan windows were -1 to 0 V relative to the saturated calomel electrode, and galvanostatic charge-discharge (GCD) voltages were 0 to -1 V. Electrochemical impedance spectroscopy (EIS) scan frequencies ranged from 10000 to 1 Hz, with a peak voltage of 1 mV. The symmetrical supercapacitor was assembled using a Swagelok apparatus, with Whatman filter paper as the diaphragm, 6MKOH solution as the electrolyte, and the aforementioned nickel foam disk electrode as the symmetrical electrode. CV, GCD, and EIS tests were performed on the symmetrical supercapacitor, and a GCD test was conducted at a charge-discharge current density of 5 A / g for 5000 cycles.

[0078] For a three-electrode system, the specific capacitance C (F / g) of the material is obtained from the GCD test results, and the calculation follows the formula:

[0079]

[0080] For a two-electrode system, the specific capacitance C (F / g) of the material is obtained from the GCD test results, and the calculation follows the formula:

[0081]

[0082] Energy density E (Wh / kg) is calculated using the following formula:

[0083]

[0084] The power density P (W / kg) is calculated using the following formula:

[0085]

[0086] The coulomb efficiency η (%) is calculated according to the following formula:

[0087]

[0088] The capacitance retention rate R (%) is calculated according to the following formula:

[0089]

[0090] Where I represents current density, Δt represents discharge time, m represents the mass of electrode active material, ΔV represents the charge / discharge potential window, considering ohmic drop, tD represents discharge time, tC represents charging time, FC represents the discharge specific capacitance of the last cycle, and IC represents the discharge specific capacitance of the first cycle.

[0091] The CV curve of porous carbon PC-10-800-none in the three-electrode system obtained by the test in Comparative Example 1 is as follows: Figure 9 As shown in Figure a, the GCD curve is as follows: Figure 9 As shown in b, the CV curve of porous carbon PC-11-800-ZnC2O4 in the three-electrode system in Comparative Example 5 is as follows. Figure 9 As shown in c, the GCD curve is as follows Figure 9 As shown in d, the CV curve of porous carbon PC-12-800-KOH in the three-electrode system in Comparative Example 6 is as follows. Figure 9 As shown in Figure e, the GCD curve is as follows Figure 9 As shown in f, the CV curve of porous carbon PC-11-800-K3[Fe(C2O4)3] in the three-electrode system in Comparative Example 7 is as follows. Figure 9 As shown in g, the GCD curve is as follows Figure 9 As shown in h, the CV curves of porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in the three-electrode system in Example 1 are as follows: Figure 9 As shown in Figure i, the GCD curve is as follows Figure 9 As shown in Figure j, the CV curves of all porous carbon samples exhibit a similar rectangular structure, indicating that the stored charge on the electrode is due to double-layer adsorption, demonstrating the mechanism of EDLC, and no pseudo-capacitive behavior was observed. The GCD curves of all porous carbon samples show a similar isosceles triangle shape, further confirming that the stored charge on the electrode is due to double-layer adsorption.

[0092] pass Figure 10 Porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in Example 1 and porous carbon in Comparative Example 1

[0093] Comparison of GCD values ​​(a) of PC-10-800-none, porous carbon PC-11-800-ZnC2O4 (Comparative Example 5), porous carbon PC-12-800-KOH (Comparative Example 6), and porous carbon PC-11-800-K3[Fe(C2O4)3] in a three-electrode system shows that, among the synthesized samples, at a current density of 1 A / g, PC-10:1:8-800-KC2O4&ZnC2O4 has the highest specific capacitance of 285.3 F / g, while PC-11-800-K3[Fe(C2O4)3] has a specific capacitance of 274.0 F / g with the largest specific surface area. This demonstrates that the design of pore distribution can optimize charge storage behavior and increase specific capacitance. The specific capacitance of PC-11-800-ZnC2O4 is relatively low at 202.0 F / g, indicating that the high proportion of mesopores and macropores is detrimental to increasing the surface area, thus limiting the specific capacitance. PC-12-800-KOH, by increasing the surface area of ​​the micropores, achieves a higher specific capacitance (253.6 F / g) than PC-11-800-ZnC2O4; however, the secondary carbonization process diminishes its utilization advantage. The specific capacitance of YP-50F is only 99.2 F / g, all lower than the samples prepared in this study. Figure 10 Porous carbon in Example 1 at a scan rate of 100 mv / s

[0094] PC-10:1:8-800-KC2O4&ZnC2O4, porous carbon in Comparative Example 1, PC-10-800-none, porous carbon in Comparative Example 5

[0095] PC-11-800-ZnC2O4, porous carbon PC-12-800-KOH in Comparative Example 6, and porous carbon in Comparative Example 7

[0096] The CV comparison diagram (b) of PC-11-800-K3[Fe(C2O4)3] in the three-electrode system shows that the sample...

[0097] The CV curve of PC-10:1:8-800-KC2O4&ZnC2O4 undoubtedly has the largest area, indicating a greater response current to voltage changes. This is attributed to the higher ion transport rate achieved through optimized pore structure design. (Sample)

[0098] The specific surface area and specific capacitance of PC-11-800-ZnC2O4 are both smaller than those of PC-12-800-KOH; however, the area of ​​its CV curve is larger, indicating a larger response current. This suggests that abundant mesoporous and macroporous structures are key factors in improving ion transport rates. Figure 10Porous carbon PC-10:1:8-800-KC2O4&ZnC2O4 in Example 1, porous carbon PC-10-800-none in Comparative Example 1, porous carbon PC-11-800-ZnC2O4 in Comparative Example 5, and porous carbon in Comparative Example 6

[0099] The EIS comparison diagram (c) of porous carbon PC-11-800-K3[Fe(C2O4)3] in the three-electrode system of PC-12-800-KOH and Comparative Example 7 shows that the sample PC-10:1:8-800-KC2O4&ZnC2O4 electrode has the lowest electronic conduction resistance (Rs) and the lowest charge transfer resistance (Rct). In the low-frequency region, it shows a vertically rising straight line, indicating that it is an ideal capacitive behavior of porous carbon electrode, and the diffusion of electrolyte in the pores of porous carbon is not hindered at all.

[0100] To investigate the performance of porous carbon samples in actual discharge scenarios of supercapacitors, the samples were...

[0101] Electrodes made of PC-10:1:8-800-KC2O4 & ZnC2O4 were used in a Swagelok device to assemble a symmetrical supercapacitor. CV, GCD, and EIS tests were performed using a Princeton electrochemical workstation, and its cycling stability was verified by 5000 charge-discharge cycles at a current density of 5 A / g. The porous carbon obtained in Example 1...

[0102] The CV curves of PC-10:1:8-800-KC2O4&ZnC2O4 on the Swagelok apparatus are as follows: Figure 11 As shown in Figure a, the GCD curve is as follows: Figure 11 As shown in b, the EIS spectrum is as follows Figure 11 As shown in c, the 5000 charge-discharge cycle diagram is as follows. Figure 11As shown in Figure d, the curves at different voltage scan rates are approximately symmetrical rectangles, demonstrating good reversible capacitive behavior. The calculated specific capacitances at current densities of 1 A / g, 2 A / g, 5 A / g, and 10 A / g are 145.1 F / g, 140.7 F / g, 126.3 F / g, and 119.1 F / g, respectively. At a current density of 10 A / g, the specific capacitance retains 82.1% of that at 1 A / g, demonstrating good rate performance, which is attributed to the well-designed three-dimensional multi-level porous structure with a reasonable pore size distribution. The calculated energy density reaches 20.2 Wh / kg at a power density of 500 W / kg, and still remains at 16.5 Wh / kg at a power density of 5000 W / kg. After 5000 charge-discharge cycles at a current density of 5 A / g, the calculated capacitance retention rate is 90.0% compared to the first cycle, and the coulombic efficiency is 100%, demonstrating excellent cycle stability. The calculated electrochemical impedance spectroscopy results in an electronic conduction resistance of 1.95Ω and a charge conduction resistance of 0.28Ω. At low frequencies, these resistances exhibit a vertically rising straight line, demonstrating ideal capacitive behavior and indicating that the charge diffuses rapidly within the pores of the porous carbon electrode.

[0103] Electrochemical tests were performed on the porous carbon PC-bagasse of Example 2 in a three-electrode system. The GCD curve of the porous carbon PC-bagasse in Example 2 in the three-electrode system is shown below. Figure 12 As shown in Figure a, the CV curve is as follows Figure 12 As shown in Figure b, the relationship between current density and capacity is as follows: Figure 12 As shown in c, the EIS spectrum is as follows Figure 12 As shown in Figure d, the GCD curve appears as an approximately isosceles triangle, indicating good double-layer behavior during charge and discharge. The specific capacitance obtained at a current density of 1 A / g is 352.0 F / g, and at a current density of 20 A / g, the specific capacitance still remains at 177.2 F / g, with a retention rate of 50.2%, which is attributed to the construction of mesopores and macropores.

[0104] The embodiments of the present invention have been described in detail above, but the present invention is not limited to the described embodiments. For those skilled in the art, various changes, modifications, substitutions, and variations can be made to these embodiments without departing from the principles and spirit of the present invention, and these variations still fall within the protection scope of the present invention.

Claims

1. A green synthesis method for preparing porous carbon for supercapacitors using a one-pot, single-stage carbonization process, characterized by: The preparation method includes the following steps: (1) Alkaline lignin is directly mixed with activators zinc oxalate and potassium oxalate in a mass ratio of 10:1:8-10:10:16 in a solid state to obtain a mixed raw material; (2) The mixed raw materials are carbonized in an inert gas environment, cooled, ground, acid-washed, water-washed, and dried to obtain porous carbon; The carbonization process employs a programmed temperature increase method, starting from room temperature and raising the temperature to 300-500 ℃, holding for 0.5-1.5 hours, and then raising the temperature to 700-1000 ℃ and holding for 1-3 hours.

2. The green synthesis method for preparing porous carbon for supercapacitors using a one-pot, single-stage carbonization process according to claim 1, characterized in that, In step (2), the programmed temperature rise refers to raising the temperature from room temperature to 400 ℃ and holding it for one hour, and then raising the temperature to 800 ℃ and holding it for two hours.

3. The green synthesis method for preparing porous carbon for supercapacitors using a one-pot, single-stage carbonization process according to claim 2, characterized in that, The heating rate is 3~15 °C / min. -1 .

4. The green synthesis method for preparing porous carbon for supercapacitors using a one-pot, single-stage carbonization process according to claim 1, characterized in that, In step (2), the flow rate of the inert gas is 100~300 ml / min. -1 .

5. The green synthesis method for preparing porous carbon for supercapacitors using a one-pot, single-stage carbonization process according to claim 1, characterized in that, In step (2), the acid washing refers to washing with HCl solution by stirring.

6. The green synthesis method for preparing porous carbon for supercapacitors using a one-pot, single-stage carbonization process according to claim 1, characterized in that, In step (2), the water washing refers to washing with deionized water until neutral.

Citation Information

Patent Citations

  • Preparation method of biomass hard carbon sodium ion battery negative electrode material with good consistency

    CN119735196A